Strategi Kepala Madrasah dalam Meningkatkan Kompetensi Sosial Guru di MTsN 3 Aceh Barat - Devi Sarwati; Herman Herman; Ade Kurniawan (Universitas Negeri Malang, 2026)
Abstract: Teachers' social competence plays an important role in creating harmonious relationships among school members and supporting the success of the educational process within the madrasah environment. This study aims to analyzing the strategy of the madrasah principalin improving teachers' social competence at MTsN 3 Aceh Barat. This study employed a descriptive qualitative approach. The research subjects including the head of the madrasah, deputy principal of madrasahand teachers of MTsN 3 Aceh Barat. Data were collected through in-depth interviews, observation, and documentation study by reviewing relevant journals and scientific sources. Data analysis was conducted descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that teachers' social competence at MTsN 3 Aceh Barat is in the good category. The principal's strategies in improving teachers' social competence were carried out through three main approaches, namely strengthening social activities within the madrasah environment, the principal's direct involvement as a role model, and continuous guidance through personal communication and routine evaluation via madrasah meetings. The exemplary behavior of the madrasah principal in various social activities has proven to be the most effective strategy in forming a culture of togetherness, solidarity, and cooperation among teachers. The conclusion of this study indicates that participative and role model-oriented leadership by the principal is capable of improving teachers' social competence in a sustainable manner within the madrasah environment. Keywords: madrasa head; teachers’ social competence; educational leadership; madrasah Abstrak: Kompetensi sosial guru memiliki peran penting dalam menciptakan hubungan yang harmonis antar warga sekolah serta mendukung keberhasilan proses pendidikan di lingkungan madrasah. Penelitian ini bertujuan untuk menganalisis strategi kepala madrasah dalam meningkatkan kompetensi sosial guru di MTsN 3 Aceh Barat. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Subjek penelitian meliputi kepala madrasah, wakil kepala madrasah, dan guru MTsN 3 Aceh Barat. Metode pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan studi dokumentasi dengan menelaah jurnal serta sumber ilmiah yang relevan. Analisis data dilakukan secara deskriptif kualitatif melalui tahapan reduksi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa kompetensi sosial guru di MTsN 3 Aceh Barat berada pada kategori baik. Strategi kepala madrasah dalam meningkatkan kompetensi sosial guru dilakukan melalui tiga pendekatan utama, yaitu penguatan kegiatan sosial di lingkungan madrasah, keterlibatan langsung kepala madrasah sebagai teladan, serta pembinaan berkelanjutan melalui komunikasi personal dan evaluasi rutin melalui rapat madrasah. Keteladanan kepala madrasah dalam berbagai aktivitas sosial terbukti menjadi strategi yang paling efektif dalam membentuk budaya kebersamaan, solidaritas, dan kerja sama antar guru. Simpulan penelitian ini menunjukkan bahwa kepemimpinan kepala madrasah yang partisipatif dan berorientasi pada keteladanan mampu meningkatkan kompetensi sosial guru secara berkelanjutan di lingkungan madrasah. Kata kunci: strategi kepala madrasah; kompetensi sosial guru; kepemimpinan pendidikan; madrasah